Physiological and proteomic analyses on artificially aged Brassica napus seed - Yin, Xiaojian; He, Dongli; Gupta, Ravi; Yang, Pingfang (Frontiers in Plant Science, 2015)
Plant seeds lose their viability when they are exposed to long term storage or controlled deterioration treatments, by a process known as seed ageing. Based on previous studies, artificially ageing treatments have been developed to accelerate the process of seed ageing in order to understand its underlying mechanisms. In this study, we used Brassica napus seeds to investigate the mechanisms of ageing initiation. B. napus seeds were exposed to artificially ageing treatment (40 oC and 90% relative humidity) and their physio-biochemical characteristics were analyzed. Although the treatment delayed germination, it did not increase the concentration of cellular reactive oxygen species (ROS). Comparative proteomic analysis was conducted among the control and treated seeds at different stages of germination. The proteins responded to the treatment were mainly involved in metabolism, protein modification and destination, stress response, development and miscellaneous enzymes. Except for peroxiredoxin, no changes were observed in the accumulation of other antioxidant enzymes in the artificially aged seeds. Increased content of ABA was observed in the artificially treated seeds which might be involved in the inhibition of germination. Taken together, our results highlight the involvement of ABA in the initiation of seed ageing in addition to the ROS which was previously reported to mediate the seed ageing process.